Strengthening community social capital for post-mining land restoration efforts: Study at PT RBT in Penyamun Village, Bangka Belitung Province, Indonesia - Herdiyanti Herdiyanti; Putra Pratama Saputra; Citra Asmara Indra; Bustami Rahman (Masyarakat, Kebudayaan dan Politik, 2022)
Indonesia is still facing various environmental problems due to increasingly massive and inappropriate mining activities. Therefore, land restoration is a basic practice in the rehabilitation of mining damage. This study aims to examine empirically the reality of the relationship between the community and PT RBT and strengthen social capital in carrying out post-mining land restoration activities. This study used the descriptive qualitative method. Data were collected through in-depth interviews and a literature study. The results showed that social relations became the main indicator in supporting the formation of trust, cooperation, and networks. Elements of social capital are packaged in the form of community participation in various post-mining land restoration activities. This is done to minimize the level of environmental damage that has increased massively, marked by the ex-mining pit that occurred in Bangka Belitung. The relationships formed are certainly expected to provide feedback for villages that run post-mining land restoration programs. This study concludes that the existence of bonding and bridging social capital that works well will facilitate the continuity of the post-mining land restoration programs.